TRIM66 promotes malignant progression of prostate carcinoma through the JAK/STAT pathway. Issue 4 (3rd March 2020) - Cao, Hongwen; Gao, Renjie; Chen, Lei; Feng, Yigeng
Abstract : Prostate cancer is the fifth leading cause of cancer‐related deaths in males globally. Tripartite Motif Containing 66 (TRIM66) functions as transcriptional repressor and exerts its effect at least partially through promotion of deacetylase. TRIM66 has been previously reported to play an oncogenic role in a number of human cancers. Here, we investigated the potential oncogenic properties of TRIM66 in prostate cancer. We report that shRNA‐mediated knockdown of TRIM66 significantly suppressed viability and proliferation of both PC‐3 and DU145 prostate cancer cell lines. Furthermore, TRIM66 deficiency inhibited migration and invasion of prostate cancer cells. Mechanistically, TRIM66 positively regulated signal transducer and activator of transcription 2 (STAT2) and interleukin‐2 (IL‐2) expression. The predominance of STAT2–IL‐2 in mediating the oncogenic properties of TRIM66 was determined using a rescue assay, wherein overexpression of either STAT2 or IL‐2 almost completely abolished the inhibitory effects on cell proliferation, migration and invasion elicited by TRIM66 deficiency in prostate cancer cells. Our study highlights the importance of the TRIM66–STAT2–IL‐2 signaling axis in the tumor biology of prostate cancer. Abstract : Tripartite Motif Containing 66 (TRIM66) knockdown suppressed viability and proliferation of prostate cancer cell lines. TRIM66 deficiency inhibited migration and invasion of prostate cancer cells. TRIM66 positively regulated signal transducer and activator of transcription 2 and interleukin‐2 expression. Our study highlights the importance of the TRIM66–signal transducer and activator of transcription 2–interleukin‐2 signaling axis in the tumor biology of prostate cancer.